A transition mass in the local Tully–Fisher relation. Issue 1 (10th July 2015) - Simons, Raymond C.; Kassin, Susan A.; Weiner, Benjamin J.; Heckman, Timothy M.; Lee, Janice C.; Lotz, Jennifer M.; Peth, Michael; Tchernyshyov, Kirill
Abstract : We study the stellar mass Tully–Fisher relation (TFR; stellar mass versus rotation velocity) for a morphologically blind selection of emission line galaxies in the field at redshifts 0.1 <  z  < 0.375. Kinematics (σg, V rot ) are measured from emission lines in Keck/DEIMOS spectra and quantitative morphology is measured from V - and I -band Hubble images. We find a transition stellar mass in the TFR, log  M * /M⊙  = 9.5. Above this mass, nearly all galaxies are rotation dominated, on average more morphologically disc-like according to quantitative morphology, and lie on a relatively tight TFR. Below this mass, the TFR has significant scatter to low rotation velocity and galaxies can either be rotation-dominated discs on the TFR or asymmetric or compact galaxies which scatter off. We refer to this transition mass as the 'mass of disc formation', M df because above it all star-forming galaxies form discs (except for a small number of major mergers and highly star-forming systems), whereas below it a galaxy may or may not form a disc.